Expert Opinion on Wetboek van Strafrecht Art 263, 264, 266 (Criminal Code) Versus Use of Birth Certificates in Petition for Cassation Number 3561 K/Pdt/2020. 05 August 2020. Juncto Determination of the Central Jakarta District Court Number 36/Pdt.P/2020. - Youngky Fernando (Community Service Journal of Law, 2023)
Whereas on February 3, 2020, there was a Central Jakarta District Court Decision. Class-1-A-Special, Decision on the Application for Determination Number 36/Pdt.P/2020. "Regarding the Application for Ratification of Freddy Widjaya (a child outside of marriage being a legitimate child in marriage) between Mrs. Lidia Herawati Rusli (Oei Mellie Nio) and the late Mr. Eka Tjipta Widjaya (Oei Ek Tjong)". Note: Based on the 1951 Marriage Manual, there was a marriage between Mrs. Lidia Herawati Rusli (Oei Mellie Nio) and the late Mr. Eka Tjipta Widjaya (Oei Ek Tjong). Whereas regarding the abovementioned determination, on December 10 2020, there was a Decision on the Application for Cassation Number 3561 K/Pdt/2020, Regarding: Request for Cancellation of the Central Jakarta District Court's Decision. Class-1-A-Special Number 36/Pdt.P/2020. On 03 February 2020, "Regarding the Application for Ratification of Freddy Widjaya (a child outside of marriage becomes a legitimate child in marriage) between Mrs. Lidia Herawati Rusli (Oei Mellie Nio) and the late Mr. Eka Tjipta Widjaya (Oei Ek Tjong)".